2017
DOI: 10.1111/all.13358
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled, dose‐finding trial with Lolium perenne peptide immunotherapy

Abstract: BackgroundA novel subcutaneous allergen immunotherapy formulation (gpASIT+™) containing Lolium perenne peptides (LPP) and having a short up‐dosing phase has been developed to treat grass pollen–induced seasonal allergic rhinoconjunctivitis. We investigated peptide immunotherapy containing the hydrolysate from perennial ryegrass allergens for the optimum dose in terms of clinical efficacy, immunogenicity and safety.MethodsThis prospective, double‐blind, placebo‐controlled, phase IIb, parallel, four‐arm, dose‐fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
(34 reference statements)
0
20
0
1
Order By: Relevance
“…Recent studies confirmed AIT with grass allergen peptides (170 μg over 3 weeks) 110,111 and depigmented polymerized allergen extracts 112 as safe and effective treatments for local AR caused by grass pollen sensitization. A maximum cumulative dose of 490 μg of the grass pollen peptides was well tolerated with only a few minor adverse reactions.…”
Section: Allerg En Immunother Apy ( Ait )mentioning
confidence: 88%
“…Recent studies confirmed AIT with grass allergen peptides (170 μg over 3 weeks) 110,111 and depigmented polymerized allergen extracts 112 as safe and effective treatments for local AR caused by grass pollen sensitization. A maximum cumulative dose of 490 μg of the grass pollen peptides was well tolerated with only a few minor adverse reactions.…”
Section: Allerg En Immunother Apy ( Ait )mentioning
confidence: 88%
“…213 Moreover, there is some evidence that AIT is cost-effective in AR with or without asthma. 214 Allergen-specific immunotherapy is usually given as subcutaneous injections 215,216 or sublingually, [217][218][219] but novel treatment forms such as peptide immunotherapy, 11,220 intralymphatic immunotherapy 11,220 and use of recombinant allergens, and immune-modulating adjuvants and nanoparticles 21,220,221 are under development.…”
Section: Novel Therapeutic Concepts In Ait For Airway Diseasementioning
confidence: 99%
“…[3][4][5][6][7][8] In addition, a number of promising small molecule drugs and vaccines are in the development pipeline. [9][10][11] This new era is now calling for the development of biomarkers and phenoand endotyping of diseases for customized patient care, which is termed stratified medicine, precision medicine, or personalized medicine. 4 Distinguishing phenotypes of a complex disease covers the observable clinically relevant properties of the disease but does not show a direct relationship to disease etiology and pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…A further development, so-called adjuvant-free allergen peptide hydrolysate, also aims to achieve a high immunological effect with reduced IgE reactivity, [79], which has so far been demonstrated for a short duration of therapy of only three weeks [113]. The follow-up field study with these peptides on 554 grass pollen-allergic adults showed a significant but only moderate clinical advantage in the primary endpoint, as well as marked effects in the secondary endpoints investigated [114].…”
Section: Modifying Hypoallergenic Recombinant Allergoidsmentioning
confidence: 99%